1989
DOI: 10.1093/jac/23.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycosides enhance the adherence of Staphylococcus aureus to HeLa cells

Abstract: Sub-lethal concentrations of aminoglycosides enhanced the adherence of Staphylococcus aureus FDA 209P to HeLa cells, whereas beta-lactams, pyridone carboxylic acid derivatives and chloramphenicol did not. Treatment with aminoglycosides also enhanced the bacterial adherence of these cells to immobilized fibronectin and laminin, and changed the bacterial cell surface to a more hydrophilic state than exists in non-treated cells. The adherence of S. aureus was not inhibited by lipoteichoic acid, extracted from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…c-di-GMP treatment inhibits S. aureus adherence to human epithelial cells. Studies examining the adherence of S. aureus to epithelial cell monolayers and the effect of potential therapeutic agents to inhibit adherence have been performed previously (4,13,30,34,35,48,63). The data from our studies showed that treatment with 2 and 20 M c-di-GMP did not show any obvious effect on adherence.…”
Section: Resultsmentioning
confidence: 58%
“…c-di-GMP treatment inhibits S. aureus adherence to human epithelial cells. Studies examining the adherence of S. aureus to epithelial cell monolayers and the effect of potential therapeutic agents to inhibit adherence have been performed previously (4,13,30,34,35,48,63). The data from our studies showed that treatment with 2 and 20 M c-di-GMP did not show any obvious effect on adherence.…”
Section: Resultsmentioning
confidence: 58%
“…The alteration of adherence by antibiotics at subminimal in hibitory concentration (sub-MIC) is con sidered to be the result of surface charac teristic changes. We have reported the ef fects of various antibiotics, especially aminoglycosides, on adherence of Sta phylococcus aureus to HeLa cells [6]. All aminoglycosides used in the previous study enhanced staphylococcal adherence to HeLa cells, whereas beta-lactams and pyridone carboxylic acid derivatives sup pressed it.…”
mentioning
confidence: 88%
“…For extraction of lipoteichoic acid (LTA), 500 ml of the overnight culture was inoculated into 4.5 L of fresh TSB and incubated for 4-5 h. Cells were harvested by centrifugation, washed in purified water, and then used for the preparation of LTA as previously described (Miyake et al, 1989). Briefly, washed S. aureus cells were treated overnight with chloroform : methanol (1 : 1 v : v) at room temperature and centrifuged.…”
Section: Extraction Of Ltamentioning
confidence: 99%
“…The adherence assay was performed as previously described (Miyake et al, 1989). Briefly, three cover slips, on which epidermal cells were cultured, were placed in a petri dish (10 x 35 mm, Falcon) and 3 ml of the bacterial suspension was added to the dish.…”
Section: Adherence Assaymentioning
confidence: 99%
See 1 more Smart Citation